Complete French grammar - Heminway, Annie (New York : McGraw Hill Education, 2016)
Unlike typical language books, this volume is a combination language guide/workbook that intends to provide the knowledge needed to understand the subject and the practice needed to master it.
The present tense of regular -er verbs -- The present tense of -ir and -re verbs -- To be and to have -- More irregular verbs -- Devoir and its many facets -- Pronominal verbs -- The passe compose -- The imparfait -- The futur simple and the futur anterieur -- The plus-que-parfair -- The present conditional and the past conditional -- Could, should, would? -- The present subjunctive and the past subjunctive -- The infinitive mood -- The presnt participle and the gerund -- The passe simple -- The passive voice -- Indirect speech -- The imperative mood -- Articles and nouns -- All the pronouns -- Adjectives and comparisons -- Demonstrative adjectives and pronouns -- Relative pronouns -- Adverbs and expressions of time, frequency, and location -- Numbers -- Pot pourri -- Review exercises.
Keywords: FRENCH LANGUAGE GRAMMAR